2021
DOI: 10.3390/ijerph18020389
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Unmet Needs among Community-Dwelling Disabled Older People from a Linkage Perspective

Abstract: One of the challenges in response to population aging is to meet needs for elderly care among older people especially for those who want to age in their homes or communities. However, disabled older people have more challenges due to their restricted mobility to access care resources than non-disabled ones. We propose a new framework based on the changing relationship between older people and their environment, in which resource linkage in elderly care utilization is emphasized. We conducted a survey with 139 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 48 publications
0
40
0
Order By: Relevance
“…Topics covered in this literature included barriers to participation [ 7 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ], unmet needs for assistance [ 7 , 8 , 9 , 20 , 21 , 22 , 23 , 24 ], human support and peer support [ 25 , 26 , 27 , 28 ], and documentation of specific programmes [ 26 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Topics covered in this literature included barriers to participation [ 7 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ], unmet needs for assistance [ 7 , 8 , 9 , 20 , 21 , 22 , 23 , 24 ], human support and peer support [ 25 , 26 , 27 , 28 ], and documentation of specific programmes [ 26 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Andrade and Andrade [ 7 ] showed that older persons with disabilities have a high proportion of unmet needs, both in the basic activities of daily life (such as bathing, dressing, walking, using the toilet, feeding, and moving in and out of bed), as well as the instrumental activities of daily life (such as managing finances, using transportation, shopping, and taking medication). In papers from Thailand [ 21 ] and China [ 22 , 23 , 24 ], specific unmet needs are highlighted: Access to available and continuous rehabilitation services local to where persons with disabilities live; State welfare or other financial support; Information for parents of children with disabilities about disability and how to provide care and opportunities for their child; Support for childcare among parents of children with disabilities; Social support and other social resources; Support for activities required for inclusion in society (e.g., communicating, doing housework, working outside, making friends); and Support to pursue employment opportunities in line with personal preferences. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, the following factors are important in the analysis of AIP in China: a community-centric setting (versus a home-centric setting); a state-led role in care provision (versus a grassroots-led role); and AIP as a family/societyoriented decision (versus as an individual right and choice). Research has revealed characteristics of AIP in China, including the presence of different community-based models of care supporting AIP (e.g., Leung and Wong 2002;Wu et al 2005;Xu and Chow 2011); preferences to and needs for community care and support of older people with different socio-economic characteristics (e.g., Liu et al 2015;Lum et al 2016;Cheng et al 2018); and significant variations in communities and their residents' AIP experiences (e.g., Gao et al 2012;Yu and Rosenberg 2017;Wu et al 2021). However, relatively under-researched is how community works as a mediator of forces at various scales to produce new care spaces within which lived experiences of AIP are shaped, whether in western or non-western contexts (Gao et al 2015;Skinner et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing number of disabled elderly and their caregivers, the impact of disabled care activities on caregivers has received widespread attention 4,5 . In developing countries, the proportion of elderly people who choose to live at home is always higher [6][7][8] . Therefore, once the elderly have physical problems and need to be taken care, family members will assume the main tasks of support and care 9,10 .…”
Section: Introductionmentioning
confidence: 99%